The Influence of Employee Performance and Quality of Public Service Land Office at the District Konawe Selatan - M. Misqi; Madjid, Rahmat; Barata, Dion Dewa (International Journal of Contemporary Sciences (IJCS), 2024)
This study aimed to examine and explain the influence of team member performance and service quality on public satisfaction at the Konawe Selatan District Land Office. This study used a survey approach with an explanatory research design. Data were collected cross-sectionally through a questionnaire. The population of this study consisted of people who received services at the Konawe Selatan District Land Office, with a sample of 70 people. Multiple Linear Regression Analysis was used to test the hypothesis. The results showed that team member performance positively and significantly influenced public satisfaction. In addition, service quality also positively and significantly influences public satisfaction. Simultaneously, team member performance and service quality significantly influenced public satisfaction. Thus, it can be concluded that improving team member performance and service quality, as reflected through service orientation and physical aspects, positively and significantly contributes to increasing public satisfaction. This can be seen from various factors such as requirements, procedures, completion time, costs/rates, product specifications, implementer competence, implementer behaviour, complaint handling, and available facilities and infrastructure.